2018
DOI: 10.22616/reep.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Mathematics to the Engineering Education in the Students’ Assessment

Abstract: Abstract:Mathematics studies have an impact on achieving the necessary outcomes in engineering education both directly and indirectly. First, mathematics serves as a tool for solving and calculating various problems. Second, mathematics studies develop mathematical competences such as the ability to ask and answer questions in and with mathematics, and the ability to deal with mathematical language and tools. More than 100 first-year students from the Faculty of Information Technology and Faculty of Engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Test results on the elementary concepts of the students from the FIT and EF are shown in Fig. 2 The results obtained in 2015 [5] showed that only 24.7 % of the first year students from FIT have received more than 70 % of the assessment score and more than 45 % of students have received less than 50 % of the score. Comparing this year test results with 2015, it can be concluded that students' knowledge in mathematics had become even worse.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Test results on the elementary concepts of the students from the FIT and EF are shown in Fig. 2 The results obtained in 2015 [5] showed that only 24.7 % of the first year students from FIT have received more than 70 % of the assessment score and more than 45 % of students have received less than 50 % of the score. Comparing this year test results with 2015, it can be concluded that students' knowledge in mathematics had become even worse.…”
Section: Resultsmentioning
confidence: 98%
“…Unfortunately, the students' interest in these courses was very small [5]. It really shows the LLU students' low organizational skills, especially setting priorities.…”
Section: Fig1 Identified Categories Of Root-cause Factors [4]mentioning
confidence: 99%
“…However, a recent survey of first-year students shows that mathematical competences acquired in secondary schools are mediocre. For example, only 1 in 6 students self-reflected to be able to think mathematically and just 10% of secondary school graduates got reasoning skills during mathematics course (Zeidmane, Rubina, 2018). Based on this and other surprising evidence, researchers conclude secondary school graduates are not ready for studies at the university (Zeidmane, Rubina, 2017).…”
Section: Introductionmentioning
confidence: 99%